Peningkatan Literasi Keuangan Islami Bagi Generasi Z Sebagai Upaya Mewujudkan Keluarga Islami Yang Berdaya Dan Berkelanjutan di Klinik Nikah Medan - Isnan Nisa Nasution (LPPI UMN AL WASHLIYAH, 2025)
Indonesia is a country with the largest Muslim population in the world that has great potential in the development of Islamic finance, because the majority of the population in Indonesia is Muslim. However, the majority of the Muslim population is inversely proportional to the low level of Islamic financial literacy, which is a serious challenge, especially among Generation Z who are approaching marriage age. The lack of understanding and knowledge about Islamic-based family economic management is often a factor causing conflict and even divorce in young marriages. This Community Service (PKM) activity aims to improve Islamic financial literacy for Generation Z as an effort to form an empowered and sustainable family according to Islamic guidance. This activity was carried out at the Medan Marriage Clinic (KLIK) with an educational-participatory approach through seminars, case studies, Islamic financial planning simulations, and pre-tests and post-tests. The results of the activity showed that out of 90 participants involved, the increase in the score regarding participant literacy from an average of 52.6 (pre-test) increased to 83.4 (post-test). In addition, participants demonstrated the ability to prepare an Islamic family financial plan and then responded to the activity with a satisfaction level above 85%. This activity shows that Islamic financial literacy education is very effective in preparing Muslims Generation in building harmonious and economically resilient Islamic families.